2017
DOI: 10.1039/c7tb02148h
|View full text |Cite
|
Sign up to set email alerts
|

Unique phenanthrenequinone imidazole-based fluorescent materials with aggregation-induced or two-photon emission

Abstract: In this work, we developed a single fluorophore core with different substituents that can exhibit either outstanding AIE or two-photon properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Fluorogens with aggregation-induced emission (AIE) characteristics have received increasing attentions in recent years. A number of AIE fluorogens have been reported. Among them, tetraphenylethylene (TPE) and its derivatives have been extensively investigated because TPE compounds can be easily synthesized and functionalized. ,, TPE molecules with either charged or reactive moieties have been successfully utilized for constructing chemo-/biosensors. The sensing mechanism is based on the manipulation of aggregation and deaggregation of AIE molecules, which is achieved with the specific chemical and enzyme-catalyzed reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorogens with aggregation-induced emission (AIE) characteristics have received increasing attentions in recent years. A number of AIE fluorogens have been reported. Among them, tetraphenylethylene (TPE) and its derivatives have been extensively investigated because TPE compounds can be easily synthesized and functionalized. ,, TPE molecules with either charged or reactive moieties have been successfully utilized for constructing chemo-/biosensors. The sensing mechanism is based on the manipulation of aggregation and deaggregation of AIE molecules, which is achieved with the specific chemical and enzyme-catalyzed reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, tetraphenylethylene (TPE) and its derivatives have been extensively investigated because TPE compounds can be easily synthesized and functionalized. ,, TPE molecules with either charged or reactive moieties have been successfully utilized for constructing chemo-/biosensors. The sensing mechanism is based on the manipulation of aggregation and deaggregation of AIE molecules, which is achieved with the specific chemical and enzyme-catalyzed reactions. Moreover, TPE molecules with targeting groups have been used for cell imaging, which possesses a low signal-to-noise ratio and can be performed without washing steps. …”
Section: Introductionmentioning
confidence: 99%
“…Liu et al have reported phenanthro­[9,10- d ]­imidazole P19 bearing an indolium moiety (Figure a) . This compound exhibited two main absorption bands at 387 and 550 nm and strong fluorescence emission at 462–550 nm with a large two-photon excitation action cross-section between 760–860 nm, owing to the ICT process caused by the indolium moiety.…”
Section: Design Of Fluorescent Sensor Based On Condensation Between P...mentioning
confidence: 99%
“…(c) Two-photon fluorescence images of the mouse liver tissues incubated with P19 (10 μM) for 1 h. (1) Mitochondrial pH 3D fluorescence images (λ exc = 800 nm, λ em = 425–475 nm); (2) mitochondrial pH 3D fluorescence images (λ exc = 800 nm, λ em = 500–550 nm); mean fluorescence intensities of the (3) blue and (4) green channels at different depths. Adapted with permission from ref . Copyright 2017 The Royal Society of Chemistry.…”
Section: Design Of Fluorescent Sensor Based On Condensation Between P...mentioning
confidence: 99%
See 1 more Smart Citation